Leaves and Tree Rings as Biomonitoring Archives of Atmospheric Mercury Deposition: An Ecophysiological Perspective - Fabrizio Monaci; Davide Baroni (Plants)
Trees mediate critical biogeochemical cycles involving nutrients, pollutants, water, and energy at the interface between terrestrial biosphere and atmosphere. Forest ecosystems significantly influence the global cycling of mercury (Hg), serving as important sinks and potential sources of re-emission through various biotic and abiotic processes. Anthropogenic Hg emissions, predominantly from industrial activities, mining, and fossil fuel combustion, have substantially altered the natural Hg cycle, intensifying ecotoxicological concerns and establishing forests as primary routes for atmospheric Hg deposition into terrestrial reservoirs. This perturbation profoundly affects global atmospheric Hg concentrations, residence times, and spatial distribution patterns. While early investigations focused on forest stands near heavily polluted areas, contemporary research has expanded to diverse ecosystems, revealing that trees provide tissues that function as temporal archives for atmospheric-terrestrial Hg exchange. Leaves capture high-resolution records of contemporary Hg dynamics at sub-annual timescales, whereas annual growth rings preserve multi-decadal chronologies of historical atmospheric exposure. Incorporating this dual temporal perspective is crucial for analysing Hg deposition trends and assessing the efficacy of environmental policies designed to control and mitigate Hg pollution. This review critically evaluates recent developments concerning the ecophysiological determinants of Hg accumulation in trees, highlighting how combined foliar and dendrochemical analytical methods strengthen our mechanistic understanding of vegetation-atmosphere Hg exchange. To enhance biomonitoring approaches, we emphasised the need for methodological standardisation, deeper integration of ecophysiological variables, and consideration of climate change implications as priority research areas. Furthermore, integrating Hg measurements with functional markers (δ13C and δ18O) and Hg isotope analyses strengthens the capacity to differentiate between physiological and environmental influences on Hg accumulation, thereby refining the mechanistic framework underlying effective tree-based Hg biomonitoring.